Genomic correlates of response to CTLA-4 blockade in metastatic melanoma - Allen, Eliezer M. van; Utikal, Jochen; Hassel, Jessica C. (Science, 2015)
Is cancer immunotherapy a private affair? Immune checkpoint blockade, a relatively new cancer treatment, substantially extends the survival of a subset of patients. Previous work has shown that patients whose tumors harbor the largest number of mutations—and thus produce a large number of “neoantigens” recognized as foreign by the immune system—are most likely to benefit. Expanding on these earlier studies, Van Allen et al. studied over 100 patients with melanoma and found a similar correlation (see the Perspective by Gubin and Schreiber). There was no evidence, however, that specific neoantigen sequences were shared by patients who responded. Science, this issue p. 207, see also p. 158. Monoclonal antibodies directed against cytotoxic T lymphocyte-associated antigen-4 (CTLA-4), such as ipilimumab, yield considerable clinical benefit for patients with metastatic melanoma by inhibiting immune checkpoint activity, but clinical predictors of response to these therapies remain incompletely characterized. To investigate the roles of tumor-specific neoantigens and alterations in the tumor microenvironment in the response to ipilimumab, we analyzed whole exomes from pretreatment melanoma tumor biopsies and matching germline tissue samples from 110 patients. For 40 of these patients, we also obtained and analyzed transcriptome data from the pretreatment tumor samples. Overall mutational load, neoantigen load, and expression of cytolytic markers in the immune microenvironment were significantly associated with clinical benefit. However, no recurrent neoantigen peptide sequences predicted responder patient populations. Thus, detailed integrated molecular characterization of large patient cohorts may be needed to identify robust determinants of response and resistance to immune checkpoint inhibitors. Melanoma patients who respond to immunotherapy do not appear to share common tumor neoantigens. [Also see Perspective by Gubin and Schreiber ] Melanoma patients who respond to immunotherapy do not appear to share common tumor neoantigens. [Also see Perspective by Gubin and Schreiber ]